“dimensionamiento de sistema de vacio acoplado a un evaporador, en función del flujo de alimentación a concentrar de solucion tanica” - Sánchez Huamaní, Luis Daniel (2016)
The present study was to determine the design parameters of a vacuum system to be using in forced circulation evaporators single or multiple stage. The vacuum system is referred to the buffer tank at the top of the evaporator (evaporation chamber) and the condenser. For the development of this study a simple experimental forced circulation evaporator with vacuum system made by 1hp pump, vacuum container 120 L capacity, and a vacuum pump 5hp is employment. As biological material use a tannic solution dilution ratio: Water / tara 3: 1 and an initial concentration of solids: 10 ° Bx. Expressions for the design of vacuum system were identified: Total Volume evacuating the evaporation system (Ve). Ve = 0,006023F1,151 + 0,0014 F en m³ Volume evacuating the vacuum buffer tank (Vp) Vp = 0,0090F1,151 +0,00216F Evacuation time in the evaporator: te = 4,2161F1,151 + 0,98 F Volumetric flow pump: θ = 13972/ (4,2161F1,151 + 0,98 F) (L/min).